Prognostic values of microRNA-130 family expression in patients with cancer: a meta-analysis and database test - Peng, Zhen; Duan, Fujiao; Yin, Jingjing; Feng, Yajing; Yang, Zhongyu; Shang, Jia (Journal of translational medicine, 2019)
Emerging evidence shows that microRNA-130 (miRNA-130) family may be useful as prognostic biomarkers in cancer. However, there is no confirmation in an independent validation study. The aim of this study was to summarize the prognostic value of miRNA-130 family (miRNA-130a and miRNA-130b) for survival in patients with cancer. The pooled hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated to estimate the association strength between miRNA-130 family expression and prognosis. Kaplan-Meier plotters were used to verify the miRNA-130b expression and overall survival (OS). A total of 2141 patients with OS and 1159 patients with disease-free survival (DFS)/progression-free survival (PFS) were analyzed in evidence synthesis. For the miRNA-130a, the overall pooled effect size (HR) was HR 1.58 (95% CI: 1.21-2.06, P < 0.001). Tissue and serum expression of miRNA-130a was significantly associated with the OS (HR = 1.54, 95% CI: 1.11-2.14, P = 0.009; HR = 1.65, 95% CI: 1.14-2.38, P = 0.008), and in gastric cancer (HR = 1.81, 95% CI: 1.34-2.45, P < 0.001). For the miRNA-13b, a statistical correlation was observed between high miRNA-130b expression and poor OS in patients with cancer (HR = 1.95, 95% CI: 1.47-2.59, P < 0.001), especially in tissue sample (HR = 2.01, 95% CI: 1.39-2.91, P < 0.001), Asian (HR = 2.55, 95% Cl: 1.77-3.69, P < 0.001) and hepatocellular carcinoma (HR = 1.87, 95% CI: 1.23-2.85, P = 0.004). The expression of miRNA-130b was significantly correlated with DFS/PFS (HR = 1.53, 95% CI: 1.31-1.77, P < 0.001), in tissue (HR = 1.98, 95% CI: 1.50-2.62, P < 0.001) and serum (HR = 1.37, 95% CI: 1.15-1.64, P < 0.001), especially in HCC (HR = 1.98, 95% CI: 1.50, 2.62, P < 0.001). In database test, a significant correlation between high miRNA-130b expression and poor OS for HCC patients was observed (HR = 1.55, 95% CI: 1.01, 2.35, P = 0.0045). The high expression of miRNA-130 family might predict poor prognosis in cancer patients. Prospectively, combining miRNA-130a and miRNA-130b may be considered as powerful prognostic predictor for clinical application.